ANTI BACTERIAL EFFICACY OF BETA ULGARISANDCINNAMOMUMZEYLANICUMAGAINST E. FAECALIS – IN VITRO STUDY - M, Arun Kumar; Raghavendra, Koti; MS, Nivedhitha (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The objective was to evaluate the in vitro antibacterial potential of Beta vulgaris and Cinnamomum zeylanicum against Enterococcus faecalis. Methods: Ethanolic extract of B. vulgaris and C. zeylanicum was subjected to microbiological assay to determine its maximum zone of inhibition using Agar disk diffusion test against E. faecalis. Results: B. vulgaris did not show any antibacterial potential against E. faecalis, whereas C. zeylanicum showed a marked and significant efficacy against E. faecalis when applied alone and also in combination with calcium hydroxide. Conclusion: C. zeylanicum can be used as an ICM, or it can be combined with CaOH2 for effective removal of bacterial pathogens inside the root canal. Keywords: Antibacterial efficacy, Beta vulgaris, Cinnamomum zeylanicum, Enterococcus faecalis